2007
DOI: 10.1590/s0104-56872007000300011
|View full text |Cite
|
Sign up to set email alerts
|

Realimentação auditiva atrasada e tratamento de gagueira: evidências a serem consideradas

Abstract: Background: there is some indication that the use of delayed auditory feedback (DAF) is a potentially helpful technique in the treatment of stuttering. Several devices for DAF are also commercially. However, not all individuals who stutter experience a positive effect on speech fluency when speaking under DAF. And those who do show a positive effect, may differ considerably as to the degree and the conditions in which the effect is seen. Therefore, the decision whether or not to attempt the use of DAF in an gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…Perhaps one should consider here the possible influence of subperceptual stuttering (i.e. differences in the acoustics and kinematics of speech production that distinguishes the perceptually fluent speech of PWS from the fluent speech of people who do no stutter) and maybe some subtle changes in intensity and fundamental frequency that can accompany the use of DAF (Van Borsel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps one should consider here the possible influence of subperceptual stuttering (i.e. differences in the acoustics and kinematics of speech production that distinguishes the perceptually fluent speech of PWS from the fluent speech of people who do no stutter) and maybe some subtle changes in intensity and fundamental frequency that can accompany the use of DAF (Van Borsel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be denied that one should take into account a number of possible side effects when considering the use of DAF (Van Borsel, Sierens, & Pereira, 2007). Among these are that DAF may slow down speech rate (Costello-Ingham, 1993;Perkins, 1979;Wingate, 1976), lead to an increase of fundamental frequency (Lechner, 1970;Soderberg, 1959) and vocal intensity (Howell, 1990), and induce elongation of the vowels (Howell, 2004;Howell et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Gagueira é multidimensional 6 , na qual inúmeros fatores, como biológicos, psicológicos e sociais interagem de forma complexa, influenciando o desenvolvimento pessoal e as interações sociais do indivíduo que gagueja. Dentre os fatores bioló-gicos, destacam-se as habilidades auditivas como um fator que influencia na fluência da fala, pois estudos mostraram a associação entre gagueira e processamento auditivo [8][9][10] e o uso da retroalimentação auditiva atrasada (RAA) no tratamento da gagueira 11 .…”
Section: Application Of Temporal Pattern Tests In Children With Persiunclassified
“…The group of individuals who reduced the word repetitions was composed of 52.6% of mild stuttering, 31.6% of moderate stuttering and 15.8% of very severe stuttering. Previous investigations have reported that the effect of DAF is better in cases of more severe stuttering in relation to mild stuttering 18,[27][28][29] .…”
Section: Discussionmentioning
confidence: 99%